Gifts as Object of Zakat in a Review of Positive Law and Islamic Law in Indonesia - Hafizah, Amelia (Interdisciplinary Explorations in Research Journal, 2024)
Abstract This research was motivated by the rise of gift zakat along with the rise of professional zakat today. As we know gifts are gifts from one person to someone else because of affection, achievements or bonuses from the results of our hard work. Some opinions say that zakat gifts have no nisab and are issued when getting without waiting for the haul. Therefore, this study aims to find out whether there are laws or propositions that can analogize gifts as objects of zakat. This research uses a type of normative legal research using a statutory approach and a conceptual approach. The data collection that the author did through literature studies, secondary legal materials that the author used includes, the Qur'an and hadith, the Compilation of Sharia Economic Law, Fatwa DSN MUI No. 3 of 2003 concerning Zakat Income and Law No. 23 of 2011 concerning Zakat Management. The primary legal material is a legal source that is not directly related to the object of research but only as a support. The results showed that in positive law, referring to article 4 paragraph 2 letter h of Law No. 23 of 2011 concerning zakat management, the gift zakat obtained from holiday allowances is included in the assets that must be zakat because it is analogous to mall zakat in the form of income and services, if the gift has reached nisab and is fully owned. In Islamic law that has been mentioned in surah Al-Baqarah verse 267, hadith narrated by At-Tarmuzi and Ibn Majah, Compilation of Sharia Economic Law Chapter III article 678 and Fatwa DSN MUI No. 3 of 2003 concerning Zakat Income, which if the gift is obtained in a halal way, can be owned, used and has reached with nisab then it has been included in the requirements of property as an object of zakat, for which 2.5% zakat must be issued. Keywords: Zakat, Gifts, Positive Law, Islamic Law Abstrak Abstrak Penelitian ini dilatarbelakangi oleh maraknya zakat hadiah seiring dengan maraknya zakat profesi pada zaman sekarang. Sebagaimana yang kita ketahui hadiah adalah pemberian dari seseorang kepada seseorang lain karena kasih sayang, prestasi ataupun bonus dari hasil kerja keras kita. Beberapa pendapat mengatakan bahwa zakat hadiah tidak memiliki nisab dan dikeluarkan ketika mendapatkan tanpa menunggu haul. Maka dari itu penelitian ini bertujuan untuk mengetahui apakah ada Undang-Undang ataupun dalil-dalil yang dapat menganalogikan hadiah sebagai objek zakat. Penelitian ini menggunakan jenis penelitian hukum normatif dengan menggunakan pendekatan perundang-undangan (Statue Approach) dan pendekatan konseptual (Conseptual Approach). Pengumpulan data yang penulis lakukan melalui studi kepustakaan (library research), bahan hukum sekunder yang penulis gunakan meliputi, Al-Qur’an dan hadis, Kompilasi Hukum Ekonomi Syariah, Fatwa DSN MUI No 3 Tahun 2003 Tentang Zakat Penghasilan dan Undang-Undang No 23 Tahun 2011 Tentang Pengelolaan Zakat. Adapun bahan hukum primer yaitu sumber hukum yang tidak berhubungan langsung dengan objek penelitian tetapi hanya sebagai pendukung. Hasil penelitian menunjukkan dalam hukum positif, merujuk pada pasal 4 ayat 2 huruf h Undang-Undang No 23 Tahun 2011 Tentang pengelolaan zakat, maka zakat hadiah yang didapatkan dari tunjangan hari raya termasuk dalam harta yang wajib zakat karena dianalogikan dengan zakat mal yang berupa pendapatan dan jasa, apabila hadiah tersebut telah mencapai nisab dan dimilikinya secara penuh. Dalam hukum Islam yang telah disebutkan dalam surah Al-Baqarah ayat 267, hadis yang diriwayatkan oleh At-Tarmuzi dan Ibn Majah, Kompilasi Hukum Ekonomi Syariah Bab III pasal 678 dan Fatwa DSN MUI No 3 Tahun 2003 Tentang Zakat Penghasilan, yang apabila hadiah tersebut didapatkan dengan cara yang halal, dapat dimiliki, digunakan dan telah mencapai dengan nisab maka telah termasuk dalam syarat harta sebagai objek zakat, yang mana wajib dikeluarkan zakatnya sebesar 2,5%. Kata Kunci : Zakat, Hadiah, Hukum Positif, Hukum Islam